Експозиційна та виставкова діяльність музеїв Волинської області (1991–2016 рр.) - Більо Л. М; Bilo, Liubomyr (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано експозиційну та виставкову роботу музеїв Волинської області впродовж 1991— 2016 рр. Простежено зміни, які відбулись у цьому напрямі музейної діяльності (проведення реекспозицій, розробка за новими підходами експозицій нових музеїв, представлення експозицій у мережі Інтернет, актуалізація тематики виставок). Визначено детермінанти, які вплинули на досліджувані процеси.The exposition and exhibition work of the museum institutions of Volyn region during 1991 -2016 is analysed in the article. The changes, that took place in this direction of the museum activities, are characterized. Among them there is the reexposition work in the already existing museums with the newest historical and regional ethnography investigations taken into consideration, the working out of the expositions of the new departments of Volyn Local History Museum and some public museums according to the modern approaches; the exposition presentation in the Internet. The attention is payed to the important part of the exposition work - the exhibition museum practice, their themes actualization.
The Exposition and Exhibition Activities of the Museums of Volyn Region (1991-2016)
Keywords: експозиція; виставка; реекспозиція; музей; музейний предмет; Волинська область; exposition; exhibition; reexposition; museum; museum item; Volyn region